ERASSt J074426.3 + 291606: prompt accretion disc formation in a 'faint and slow' tidal disruption event. Issue 3 (16th January 2023) - Malyali, A; Liu, Z; Merloni, A; Rau, A; Buchner, J; Ciroi, S; Di Mille, F; Grotova, I; Dwelly, T; Nandra, K; Salvato, M; Homan, D; et al.
ABSTRACT: We report on multiwavelength observations of the tidal disruption event (TDE) candidate eRASSt J074426.3 + 291606 (J0744), located in the nucleus of a previously quiescent galaxy at z = 0.0396. J0744 was first detected as a new, ultra-soft X-ray source (photon index ∼4) during the second SRG /eROSITA All-Sky Survey (eRASS2), where it had brightened in the 0.3–2 keV band by a factor of more than ∼160 relative to an archival 3σ upper limit inferred from a serendipitous Chandra pointing in 2011. The transient was also independently found in the optical by the Zwicky Transient Facility (ZTF), with the eRASS2 detection occurring only ∼20 d after the peak optical brightness, suggesting that the accretion disc formed promptly in this TDE. Continued X-ray monitoring over the following ∼400 d by eROSITA, NICER XTI and Swift XRT showed a net decline by a factor of ∼100, albeit with large amplitude X-ray variability where the system fades, and then rebrightens, in the 0.3–2 keV band by a factor ∼50 during an 80-d period. Contemporaneous Swift UVOT observations during this extreme X-ray variability reveal a relatively smooth decline, which persists over ∼400 d post-optical peak. The peak observed optical luminosity (absolute g -band magnitude ∼−16.8 mag) from this transient makes J0744 the faintest optically detected TDE observed to date. However, contrasting the known set of 'faint and fast' TDEs, the optical emission from J0744 decays slowly (exponential decay time-scale ∼120 d), making J0744 the first member of a potential new class of 'faint and slow' TDEs.